The Association of Primary Open Angle Glaucoma and Ocular Hypertension with Anti-VEGF Injections - LoBue SA; Albear S; Martin C; Guagliardo A; Chang T (Clinical Ophthalmology)
Stephen A LoBue,1,2 Sinan Albear,1,2 Curtis Martin,1 Alan Guagliardo,1 Tom Chang1 1Department of Ophthalmology, Acuity Eye Group, Pasadena, CA, USA; 2Department of Ophthalmology, SUNY Downstate Medical Center, Brooklyn, NY, USACorrespondence: Tom Chang, Acuity Eye Group, Vitreoretinal Surgeon, 100 E California Blvd, Pasadena, CA, 91105, USA, Email tchang@acuityeyegroup.comPurpose: To study the effects of anti–VEGF injections on the prevalence of ocular hypertension (OHT), sustained elevated intraocular pressure (SE-IOP), and primary open-angle glaucoma (POAG) with age-matched controls.Methods: A retrospective case-control study was performed with neovascular age-related macular degeneration (AMD) or diabetic macular edema (DME) against a control group involving atrophic AMD or diabetic retinopathy (DR) without DME. Bevacizumab, ranibizumab, or a combination of both were used in the treatment group. OHT was defined as IOP> 21 mm Hg while SE-IOP was defined as IOP that increased by > 6 mmHg or was > 25 mm Hg on two or more visits, 30 days apart. Patients with a pre-existing history of glaucoma, vein occlusions, IVI steroids, and pars plana vitrectomy were excluded.Results: A total of 1312 eyes of 784 patients were included in the study. Using age-matched controls, the treatment and control group was further refined to 394 eyes of 224 patients compared to 340 eyes from 170 patients respectively. The mean age was 58.4 ± 8.7 for the control versus 58.8 ± 8.8 years for the treatment group. The average IOP was higher in the injection group compared to the control with 25.8 ± 9.3 versus 19.5 ± 5.1 mmHg respectively, P< 0.001. Significant increases in POAG (10.7% vs 2.9%, p< 0.01), OHT (67.0% vs 22.4%, p< 0.001), and SE-IOP (41.1% vs 7.6%, p< 0.001) were seen in the injection group compared to the age-matched control group. The rates of POAG and OHT were positively associated with the number of injections, R2=0.856, P< 0.01 and R2=0.749, P< 0.05, respectively.Conclusion: Compared to age-matched controls, patients treated with anti-VEGF agents demonstrated an increased rate of OHT, SE-IOP, and POAG which correlated with the number of IVIs. However, additional prospective studies are needed to determine if there is a true association between intravitreal anti-VEGF injections and glaucoma.Keywords: intravitreal injection, IVI, sustained-elevated intraocular pressure, SE-IOP, primary open-angle glaucoma, POAG, age-related macular degeneration, AMD